Training In Porang Meat Ball Production At Klangon Village, Saradan District, Madiun Regency - Simon Bambang Widjanarko; Sri Winarsih; Susinggih Wijana; Mimin Suryani (Journal of Innovation and Applied Technology, 2019)
Purification method on crude porang flour, using with multistage ethanol washing technique, resulted purified  porang flour which can be used for meatballs production. The objective of this paper was to deliver scientific knowledge on formulating meat ball ingredients as well as to demonstrate and to carry out a practical work on making  a meat balls using mixture gels of composite flour contained porang flour and k-carrageenan flour. The extensions process was conducted at a community family welfare organization (CFWO), Klangon Village, Saradan Distric, Madiun Region and Pandan Asri Community Village Forest Organization at Klangon Village, Saradan Distric, Madiun Region. Finally, the extension activities resulted deep awareness for a targeted people in maximixing the use of porang bulbs for food preparations and the product can be sold as processed food. This activity will support Local Government Wisdom as stated: “one village one product”.